Proceedings of the Seventeenth Annual ACM-SIAM Symposium on Discrete Algorithm - SODA '06 2006
DOI: 10.1145/1109557.1109654
|View full text |Cite
|
Sign up to set email alerts
|

Quantum verification of matrix products

Abstract: We present a quantum algorithm that verifies a product of two n×n matrices over any integral domain with bounded error in worst-case time O(n 5/3 ) and expected time O(n 5/3 / min(w,where w is the number of wrong entries. This improves the previous best algorithm [ABH + 02] that runs in time O(n 7/4 ). We also present a quantum matrix multiplication algorithm that is efficient when the result has few nonzero entries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
132
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 21 publications
0
132
0
1
Order By: Relevance
“…For examples, in quantum information science, the DTQW is used as the quantum-speedup algorithms [5,8,52,53]. The Grover algorithm, which is the spatially search algorithm, can be taken as the tool of the DTQW [68].…”
Section: Review Of Discrete Time Quantum Walkmentioning
confidence: 99%
“…For examples, in quantum information science, the DTQW is used as the quantum-speedup algorithms [5,8,52,53]. The Grover algorithm, which is the spatially search algorithm, can be taken as the tool of the DTQW [68].…”
Section: Review Of Discrete Time Quantum Walkmentioning
confidence: 99%
“…Optical multiport interferometers provide an attractive implementation for quantum walks, since optical fields naturally exhibit coherence between pathways and allow multi-walker scenarios using multiple single photons. However, this approach is susceptible to losses, which limit the achievable scale before being overtaken by noise, and which abrogate many of the advantages implied for applications in quantum information processing [4][5][6][7][8][9][10][11][12]. This challenge motivates the development of low-loss, modular, guided-wave interferometer networks for quantum walks.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], it was shown that the quantum walk on the so-called "glued trees" graph reaches the final vertex from the initial vertex exponentially faster that a similar classical walk. Other algorithms based on quantum walks include matrix product verification [8], triangle finding [9] and group commutativity testing [10].…”
Section: Introductionmentioning
confidence: 99%